2020
DOI: 10.1111/pace.13913
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular arrhythmia suppression with ivabradine in a patient with catecholaminergic polymorphic ventricular tachycardia refractory to nadolol, flecainide, and sympathectomy

Abstract: Conventional treatment strategies for catecholaminergic polymorphic ventricular tachycardia (CPVT) include avoidance of strenuous exercise and competitive sports, drugs such as ß-blockers and flecainide and, cervical sympathectomy. An implantable cardioverter-defibrillator (ICD) has been utilized if the response to these strategies is inadequate; however, ICD use in CPVT patients, in addition to usual complications, is associated with an increased risk of life-threatening electrical storm. Ivabradine is a sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…A weak frequency dependence may also serve as an explanation that changes in QRS duration by ivabradine were not rate-dependent ( Amstetter et al, 2021 ). In any case, ivabradine was recently shown to control catecholaminergic polymorphic ventricular tachycardia ( Vaksmann and Klug, 2018 ; Kohli et al, 2020 ) and junctional ectopic tachycardia ( Al-Ghamdi et al, 2013 ; Dieks et al, 2016 ; Kumar et al, 2017 ; Ergul et al, 2018 ; Ergul and Ozturk, 2018 ; Mert et al, 2018 ; Janson et al, 2019 ; Kumar et al, 2019 ). While some of these arrhythmias may be of automatic origin, potentially tied to the function of HCN channels, the antiarrhythmic activity of ivabradine could also stem from the inhibition of VGSCs, in particular under ischemic conditions and in the failing heart, when resting membrane potentials are substantially depolarized ( Bean et al, 1983 ) and channel block would be favored ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A weak frequency dependence may also serve as an explanation that changes in QRS duration by ivabradine were not rate-dependent ( Amstetter et al, 2021 ). In any case, ivabradine was recently shown to control catecholaminergic polymorphic ventricular tachycardia ( Vaksmann and Klug, 2018 ; Kohli et al, 2020 ) and junctional ectopic tachycardia ( Al-Ghamdi et al, 2013 ; Dieks et al, 2016 ; Kumar et al, 2017 ; Ergul et al, 2018 ; Ergul and Ozturk, 2018 ; Mert et al, 2018 ; Janson et al, 2019 ; Kumar et al, 2019 ). While some of these arrhythmias may be of automatic origin, potentially tied to the function of HCN channels, the antiarrhythmic activity of ivabradine could also stem from the inhibition of VGSCs, in particular under ischemic conditions and in the failing heart, when resting membrane potentials are substantially depolarized ( Bean et al, 1983 ) and channel block would be favored ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analyses suggested an increased risk of atrial fibrillation associated with ivabradine treatment ( Martin et al, 2014 ; Tanboğa et al, 2016 ; Mengesha et al, 2017 ). On the other hand, ivabradine was able to control ventricular arrhythmias in catecholaminergic polymorphic ventricular tachycardia ( Vaksmann and Klug, 2018 ; Kohli et al, 2020 ) and junctional ectopic tachycardia ( Al-Ghamdi et al, 2013 ; Dieks et al, 2016 ; Kumar et al, 2017 ; Ergul et al, 2018 ; Ergul and Ozturk, 2018 ; Mert et al, 2018 ; Janson et al, 2019 ; Krishna et al, 2019 ; Kumar et al, 2019 ). Recently, ivabradine has also been considered as a rate control therapy for atrial fibrillation ( Moubarak et al, 2014 ; Kosiuk et al, 2015 ; Turley et al, 2016 ; Wongcharoen et al, 2016 ; Fossati et al, 2017 ), with a current clinical trial to test for this potential new indication ( Fontenla et al, 2019 ), and for other forms of atrial and ventricular tachyarrhythmias [e.g., ( Cohen et al, 2020 ; Kohli et al, 2020 )].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ivabradine is approved as an adjunctive medication to GDMT in patients with HFrEF and NYHA class II-III symptoms following the results of the SHIFT trial, which demonstrated a reduction in heart failure hospitalizations and subsequently cardiovascular death [ 148 ]. Given its unique electrophysiologic effects to reduce heart rate, a small randomized crossover trial of 21 patients found improvement in symptoms if patients with inappropriate sinus tachycardia [ 149 ]. Recent case reports document ivabradine as an effective adjunctive agent in CPVT refractory to nadolol, flecainide, and cervical sympathectomy [ 150 , 151 ].…”
Section: Medications Outside Of the Classification Systemmentioning
confidence: 99%
“…Kohli et al . suggested that ivabradine could be an important add-on therapy for CPVT patients, who are drug-refractory or unable to continue conventional therapies [ 75 ]. Using CASQ2 D307H/D307H mice and iPSC-CM, Bueno-Levy et al .…”
Section: Anagement Of Catecholaminergic Polymorphic Ventricular Tachycardiamentioning
confidence: 99%